1992
DOI: 10.1002/j.1460-2075.1992.tb05587.x
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase homologue Ste20p is required to link the yeast pheromone response G-protein beta gamma subunits to downstream signalling components.

Abstract: In the yeast Saccharomyces cerevisiae the G‐protein beta gamma subunits have been shown to trigger downstream events of the pheromone response pathway. We have identified a new gene, designated STE20, which encodes a protein kinase homologue with sequence similarity to protein kinase C, which is required to transmit the pheromone signal from G beta gamma to downstream components of the signalling pathway. Overproduction of the kinase suppresses the mating defect of dominant‐negative G beta mutations providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
354
1
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(363 citation statements)
references
References 44 publications
7
354
1
1
Order By: Relevance
“…The speci®city of the antiserum was veri®ed, since immunoprecipitation was blocked when the antiserum was preincubated with recombinant GST-KHS ( Figure 3a). This antiserum was also able to speci®cally immunoprecipitate a 95 kD protein from metaboli- (Katz et al, 1994;Creasy and Cherno , 1995;Cvrckova et al, 1995;Leberer et al, 1992;Ramer and Davis, 1993;Freisen et al, 1994;Marcus et al, 1995;Bagrodia et al, 1995;Knaus et al, 1995;Manser et al, 1994Martin et al, 1995;Ottilie et al, 1995). Catalytic domains are boxed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The speci®city of the antiserum was veri®ed, since immunoprecipitation was blocked when the antiserum was preincubated with recombinant GST-KHS ( Figure 3a). This antiserum was also able to speci®cally immunoprecipitate a 95 kD protein from metaboli- (Katz et al, 1994;Creasy and Cherno , 1995;Cvrckova et al, 1995;Leberer et al, 1992;Ramer and Davis, 1993;Freisen et al, 1994;Marcus et al, 1995;Bagrodia et al, 1995;Knaus et al, 1995;Manser et al, 1994Martin et al, 1995;Ottilie et al, 1995). Catalytic domains are boxed.…”
Section: Resultsmentioning
confidence: 99%
“…STE20 (Leberer et al, 1992;Ramer and Davis, 1993) is involved in MAP kinase pathways regulating mating pheromone response and regulating haploid invasiveness and diploid pseudohyphal formation (initiating signals unknown) (Liu et al, 1993;Roberts and Fink, 1994;Herskowitz, 1995). Epistatically, it is positioned immediately downstream of the heterotrimeric G protein (encoded by STE4, STE18, and GPA) and upstream of the module of kinases including STE11, STE7, and FUS3 or KSS1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A homology search using the Smith-Waterman algorithm (Smith and Waterman, 1981) on the MPsearch network service program revealed that YSK1 shows signi®cant sequence identify to the kinase domains of the Ste20-related kinases (Table 2) MST1 (57% identity), a human protein kinase homologous to Ste20, possibly negatively regulated by phosphorylation ; Sps1 (53% identity), an upstream kinase of the budding yeast MAPK pathway that is involved in spore wall formation (Friesen et al, 1994;Krisak et al, 1994); GCK (52% identity), which is characteristically expressed in the germinal center of the lymphoid follicles and is involved in the regulation of the JNK/ SAPK pathway (Katz et al, 1994;Pombo et al, 1995); Ste20 (46% identity), which is activated upon stimulation of the heterotrimeric G-protein-coupled pheromone receptor and leads to the activation of the Fus3/Kss1 subgroup of yeast MAPKs (Leberer et al, 1992); PAK (44% identity), which is the ®rst identi®ed mammalian relative of Ste20 and activated by the binding of the ras-related small G-proteins Rac1 and Cdc42 (Manser et al, 1994); Cla4 (44% identity), which is involved in budding and cytokinesis in yeast, and interacts with Cdc42 (Cvrckova et al, 1995; and Shk1 (41% identity), a Ste20 homologue of ®ssion yeast, whose interaction with Cdc42 is required for normal cell morphology and mating (Marcus et al, 1995) (Figure 2b). In particular, the overall structures of YSK1, MST1, Sps1, and GCK are very similar.…”
Section: Ysk1 Is Homologous To Ste20-related Kinasesmentioning
confidence: 99%
“…In budding yeast, Ste20 is activated by the bg complex released from the heterotrimeric G protein complex upon pheromone receptor stimulation, and in turn activates Ste11 (a MAPKKK) (Leberer et al, 1992;Ramer and Davis, 1993). Cla4, a recently identi®ed novel Ste20-like protein kinase, is required for bud site establishment and cytokinesis.…”
Section: Introductionmentioning
confidence: 99%